Analysis of Gongseng Dam Break-Induced Flood in East Java, Indonesia Through 2D Iber Software - Ahmadi, Sa’iyd Husayn; Triatmodjo, Bambang; Benazir (Journal of the Civil Engineering Forum, 2023)
The dam is a crucial river-crossing structure that ensures a sustainable water supply and offers numerous benefits. However, the potential hazard of dam failure is an imminent threat that could materialize unexpectedly. To comprehend the potential impact of dam break flood and identify vulnerable areas, it is essential to conduct rigorous analysis and simulate various dam failure scenarios. This comprehensive assessment is invaluable for informed land use planning and the development of effective emergency response plans. Therefore, this study aimed to analyze flood inundation resulting from the hypothetical failure of Gongseng dam, using Iber model. The modeling approach relied on a two-dimensional finite volume shallow water model, guided by specialized software. The scenarios for Gongseng dam break showed inundation areas of 12.57 km² and 7.55 km² for overtopping and piping failure, respectively. Overtopping failure resulted in the highest discharge, with Von Thun method causing severe damage due to wide break dimensions, and eventually leading to catastrophic consequences. However, this study showed that Froehlich method provided the most rational prediction for break parameters. In contrast to the other methods focusing solely on water height behind dam, Froehlich equation considered both the volume and height at the time of failure. Implementing dam break analysis held the potential to benefit downstream communities by providing inundation maps, thereby aiding in the mitigation of flood risks. Particularly, in situations with limited data and resources, as shown in this study, the cost-effective modeling method proposed could be an attractive option for simulating extreme flood induced by dam break.